CLIMATE JUSTICE IN URBAN AMAZONIA: A CRITICAL ANALYSIS OF SOCIO-ENVIRONMENTAL VULNERABILITIES AND THE ROLE OF COP30 IN BELÉM - Suzuki, Gilberto Takashi; do Nascimento Silveira, Jairton Dimas; Lapa, Magno Rodrigues Pedreira; da Silva, Silvia Pires; Silva, Wilson Ricardo Cardoso (Seven Editora, 2025)
This theoretical essay critically examines socio-environmental vulnerabilities in urban areas of the Amazon, focusing on Belém and the upcoming COP30. The Amazon region, vital to the global climate, faces growing challenges due to climate change and disorderly urban expansion. Climate justice is imperative to ensure equity in the distribution of the burdens and benefits of climate policies, especially for disproportionately affected marginalized populations. Amazonian urbanization, driven by deforestation and migration, creates cities with poor infrastructure and high exposure to extreme weather events. COP30 in Belém is a unique opportunity to refocus global climate discussions by integrating local perspectives and the needs of Amazonian communities. We argue that socio-environmental vulnerability in Belém reflects historical and structural inequalities that limit adaptation and resilience. We propose an analytical framework to understand the intersection between climate justice, urbanization, and vulnerability in the Amazon, emphasizing participatory and fair approaches to policy. We fill a gap in the literature by focusing on the urban dimension of the Amazon climate crisis, offering insights for climate governance and sustainable urban development. We conclude that COP30 should catalyze concrete actions to promote climate justice, urban resilience, and the protection of the rights of vulnerable communities in the urban Amazon, transforming global discourse into locally relevant and equitable solutions. DOI: https://doi.org/10.56238/sevened2025.029-040